Catalytic mechanism and properties of pyridoxal 5′-phosphate independent racemases: how enzymes alter mismatched acidity and basicity. Issue 12 (17th April 2019) - Fischer, Conrad; Ahn, Yeong-Chan; Vederas, John C.
Abstract : Understanding of the mechanistic details and distal substrate site recognition characteristics can guide the design of next generation inhibitors for PLP-independent racemases. Abstract : Covering: up to March 2019 Amino acid racemases and epimerases are key enzymes that invert the configuration of common amino acids and supply many corresponding d -isomers in living organisms. Some d -amino acids are inherently bioactive, whereas others are building blocks for important biomolecules, for example lipid II, the bacterial cell wall precursor. Peptides containing them have enhanced proteolytic stability and can act as important recognition elements in mammalian systems. Selective inhibition of certain amino acid racemases ( e.g. glutamate racemase) is believed to offer a promising target for new antibacterial drugs effective against pathogens resistant to current antibiotics. Many amino acid racemases employ imine formation with pyridoxal phosphate (PLP) as a cofactor to accelerate the abstraction of the alpha proton. However, the group reviewed herein achieves racemization of free amino acids without the use of cofactors or metals, and uses a thiol/thiolate pair for deprotonation and reprotonation. All bacteria and higher plants contain such enzymes, for example diaminopimelate epimerase, which is required for lysine biosynthesis in these organisms. This process cannot be accomplished without an enzyme catalyst as the acidities of a thiol and the substrate α-hydrogen are inherently mismatched by at least 10 orders of magnitude. This review describes the structural and mechanistic studies on PLP-independent racemases and the evolving view of key enzymatic machinery that accomplishes these remarkable transformations.